2012
DOI: 10.1007/s00421-012-2406-9
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of different surface regions for thermal comfort in humans

Abstract: In a previous study, we investigated the contribution of the surface of the face, chest, abdomen, and thigh to thermal comfort by applying local temperature stimulation during whole-body exposure to mild heat or cold. In hot conditions, humans prefer a cool face, and in cold they prefer a warm abdomen. In this study, we extended investigation of regional differences in thermal comfort to the neck, hand, soles, abdomen (Experiment 1), the upper and lower back, upper arm, and abdomen (Experiment 2). The methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 19 publications
3
50
0
Order By: Relevance
“…Nevertheless, it is well accepted that thermal comfort is often intimately related to skin and core temperatures. At normothermic core temperatures, thermal comfort is largely determined by skin temperature (Gagge et al., ; Cabanac et al., , ; Mower, ; Bulcao et al., ; Pellerin et al., ; Yao et al., ; Nakamura et al., , ). However, should core temperature be displaced from normothermia, thermal discomfort ensues, while improvements in thermal comfort occur as a result of a thermal stimulus (i.e., skin cooling or warming) that aims to restore normothermia (Chatonnet & Cabanac, ; Cabanac et al., ; Mower, ; Attia & Engel, , ).…”
Section: Subjective Thermal Perception During Exercise In the Heatmentioning
confidence: 99%
“…Nevertheless, it is well accepted that thermal comfort is often intimately related to skin and core temperatures. At normothermic core temperatures, thermal comfort is largely determined by skin temperature (Gagge et al., ; Cabanac et al., , ; Mower, ; Bulcao et al., ; Pellerin et al., ; Yao et al., ; Nakamura et al., , ). However, should core temperature be displaced from normothermia, thermal discomfort ensues, while improvements in thermal comfort occur as a result of a thermal stimulus (i.e., skin cooling or warming) that aims to restore normothermia (Chatonnet & Cabanac, ; Cabanac et al., ; Mower, ; Attia & Engel, , ).…”
Section: Subjective Thermal Perception During Exercise In the Heatmentioning
confidence: 99%
“…Nakamura et al [13], using stimulated hot and cold conditions, found that humans prefer a cooler face and warmer abdomen, respectively. They also reported that the distal region (e.g., limbs and extremities) is less sensitive to changes in thermal pleasantness than the trunk [14]. Interestingly, the phenomenon of cold limbs is reported to have a genetic basis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies indicate that there are regional differences in the thermal comfort response to thermal stimuli. Nakamura et al 30,31 reported that the limb and extremities are less influential for producing thermal comfort than the trunk areas; during mild heat exposure, facial and neck cooling was judged the most comfortable. Based on their influence on whole-body sensation, Zhang 32 reported that the most influential body parts are back, chest, and pelvis.…”
mentioning
confidence: 99%
“…Local cooling was applied to the head (together with the neck) and upper back because cooling of these parts has been shown to be effective in improving the thermal comfort of subjects who were awake. [30][31][32][33][34][35] The lower body sections were not cooled as people are most comfortable with warm feet 32 and warm feet have been shown to promote the rapid onset of sleep. 39 Wyndham observed that the daytime temperature for comfort (26.6°C) was higher than the nighttime comfort temperature (24.7°C) in the hot humid tropics of Australia when air-conditioning…”
mentioning
confidence: 99%